Myopia and age-related macular degeneration: structural and anatomical changes of the eye - I. B. Alekseev; Ju. A. Nam (Российский офтальмологический журнал, 2019)
The purpose of the study was to find out how age-related macular degeneration and medium-high degree myopia affect the structural and anatomical parameters of the eyeball, and to find whether a relationship exists between various types of myopic staphylomas and changes of visual functions.Material and methods. 120 patients (236 eyes), with medium and high degree myopia and age-related retinal changes, aged 44 to 81 years were tested for two groups of parameters: quantitative and qualitative. The former included the patients’ age, best corrected visual acuity (BCVA), computer perimetry data, the axial length, and the thickness of the retina in the central zone. The latter included retinal changes, in particular pigment epithelium (PE) defects, drusen, PE detachment, choroidal neovascular membrane (CNV), Fuchs spot and diffuse chorioretinal atrophy. The impact of various types of staphylomas on visual functions was evaluated. Results. Visual functions were found to directly depend on retinal PE integrity. If defects, detachment, or drusen are present, computer perimetry parameters and BVCA are reducing. Fuchs spot presence and diffuse chorioretinal atrophy reduces BCVA and causes an MD decrease. The lowest visual acuity and considerable light sensitivity loss was noted in patients with combined staphylomas. Conclusion. The obtained data confirm that retinal dystrophic processes directly affect visual functions: BCVA and retinal photosensitivity levels drop in all retinal changes studied. The presence of staphyloma, being a factor that aggravates myopia, undoubtedly worsens the most of the parameters studied.